2016
DOI: 10.1007/s40069-016-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance and Stress–Strain Relationships for Grouted Splices Under Tensile and Cyclic Loadings

Abstract: Experimental studies were conducted on 36 grouted splices to investigate their mechanical performance under four loading schemes: (1) incremental tensile loading, (2) repeated tensile loading, (3) cyclic loading at high stress, and (4) cyclic loading at large strain. Load-deformation responses of the grouted splices under cyclic loadings were featured with pinching effect and stiffness degradation compared to those responses under tensile loadings. The shape of the hysteresis loops of load-deformation curves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…e dynamic increase factor (DIF) can be determined by Equation (8). Based on existing researches [24,25] and experimental results, the logarithmic relationship is used to characterize the relationship between strain rate and DIF, as shown in Equation (9).…”
Section: Dynamic Increase Factormentioning
confidence: 99%
See 1 more Smart Citation
“…e dynamic increase factor (DIF) can be determined by Equation (8). Based on existing researches [24,25] and experimental results, the logarithmic relationship is used to characterize the relationship between strain rate and DIF, as shown in Equation (9).…”
Section: Dynamic Increase Factormentioning
confidence: 99%
“…Most research on properties of concrete subjected to high strain rate loadings has focused on compressive strength. It is generally accepted that there is a strength increase with the increase in strain rate [7][8][9]. Mindess [10] found that an increase in the strain rate leads the elastic modulus to increase.…”
Section: Introductionmentioning
confidence: 99%
“…reduction coefficient of bearing capacity (α) is found to be 0.98, which indicates that the bearing capacity of the grouted sleeve splice is slightly lower than the tensile capacity of the connecting steel bar itself. This can be attributed to the failure mode and eccentricity of the embedded bars [41,42], as showed in Fig. 22.…”
Section: Analytical Analysismentioning
confidence: 99%
“…Due to the influences of the grouted sleeve and eccentricity of connecting steel bars [41], the ultimate bearing capacity of the specimen is different from the ultimate bearing capacity of the steel bar (see Fig. 21), which has the following relationship:…”
Section: Analytical Analysismentioning
confidence: 99%
“…Grouted splice sleeves have been the proprietary products (Haber et al 2015;Jansson 2008;Lin and Wu 2016) owned by several international companies. Designing the sleeves have been the works of specialists.…”
Section: Introductionmentioning
confidence: 99%